(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Recruitment and selection lie at the heart of how businesses procure human resource required to maintain a sustainable competitive advantage over its competitors. Staffing personnel and especially managerial personnel in the organizations may well represent one of the most important human resource management functions. Information technology essentially refers to the digital processing, storage and communication of information of all kinds. The IT sector is likely to give employment to 9 million people in India by 2008 and also generate 87 billion in annual revenues and 225 billion in market in India by 2008. The present article focuses on how efficiently the IT sector follows the Recruitment selection processes and to trace out the differences of the same between the Indian MNC companies if any.